Adverse events related to neuromuscular blocking agents: a disproportionality analysis of the FDA adverse event reporting system - Li, Liangxia; Xu, Qianqian; Liu, Yarui; Pang, Liangfang; Cui, Zhou; Lu, Yuanyuan (Frontiers in Pharmacology, 2024)
Background: Neuromuscular blocking agents (NMBAs) are primarily used during surgical procedures to facilitate endotracheal intubation and optimize surgical conditions. This study aimed to explore the adverse event signals of NMBAs, providing reference for clinical safety.This study collected reports of atracurium, cisatracurium, rocuronium, and vecuronium as primary suspect drugs in The US Food and Drug Administration Adverse Event Reporting System (FAERS) from the first quarter of 2004 to the third quarter of 2023. The adverse events (AEs) reported in the study were retrieved based on the Preferred Terms (PTs) of the Medical Dictionary for Regulatory Activities. In addition, we conducted disproportionality analysis on relevant reports using the reporting odds ratio (ROR) method and Bayesian confidence propagation neural network (BCPNN) method. A positive signal was generated when both algorithms show an association between the target drug and the AE.Results: A total of 11,518 NMBA-related AEs were reported in the FAERS database. The most AEs of rocuronium were collected. NMBA-related AEs involved 27 different system organs (SOCs), all of the four NMBAs had positive signals in "cardiac disorders", "immune system disorders", "respiratory, thoracic and mediastinal disorders" and "vascular disorders". At the PTs level, a total of 523 effective AEs signals were obtained for the four NMBAs. Cisatracurium had the fewest risk signals and demonstrated a superior safety profile. AEs labled in the instructions such as anaphylaxis (include anaphylactic reaction and anaphylactic shock), bronchospasm, respiratory arrest and hypotension were detected positive signals among all NMBAs. In addition, we also found some new AEs, such as ventricular fibrillation for the four NMBAs, hyperglycaemia for atracurium, kounis syndrome and stress cardiomyopathy for rocuronium, hepatocellular injury for cisatracurium, hyperkalaemia for vecuronium. To further investigated the AEs associated with serious clinical outcomes, we found that cardiac arrest and anaphylaxis were the important risk factors for death due to NMBAs Conclusion: NMBA-related AEs have a significant potential to cause clinically severe consequences.Our study provides valuable references for the safety profile of NMBAs, and considering the limitations of the FAERS database, further clinical data are needed to validate the findings of this study.